Robert Lecourt: The ECJ judge as journalist and political organiser - William Phelan (Trinity College Dublin, The University of Dublin, Trinity Research in Social Sciences (TRiSS), 2020)
Robert Lecourt is recognised as one of the European Court of Justice's most influential judges between 1962 and 1976. Previous research has drawn connections between the legal doctrines established by the Court in the early 1960s and the contents of the doctoral dissertation on French property law that Lecourt completed in 1931. This paper examines Lecourt's contributions to Route des Jeunes, a monthly periodical aimed at French Christian Democrats between 1935 and 1939. It demonstrates Lecourt's involvement in a Christian Democratic milieu that criticised traditional concepts of sovereignty and supported the idea of a legally-binding international community. Lecourt's extensive experience in political organizing, partisan journalism, and propaganda for French Christian Democrats may also have informed Lecourt's approach to networking and publicity after his appointment as judge and later President of the European Court of Justice.
Keywords: 330; Robert Lecourt; European Court of Justice; European Law; Legal History; Christian Democracy; Judicial Biography; Parti Démocrate Populaire